ANALISIS DAN OPTIMASI SUDU SKEA 5 KW UNTUK PEMOMPAAN - Atmadi, Sulistyo; Fitroh, Ahmad Jamaludin (BRIN Publishing, 2010)
LAPAN Wind Energy Conversion System (WECS) for pumping (SKEA-MARUTO) has a rotor diameter of 4.5 m and 6 number of blades. The blade used is a curved plate area. The result of recalculation has shown that operational condition on 10 m/sec wind speed and 100 rpm rotational speed, the rotor produces 4.74 kW. By assuming of 20% generator losses, the SKEA will produces power of 3.79 kW. To improve this performance to 5 kW, the rotor diameter has to be increased to 6 m. Chord and twist distribution are made similar to the previous design, and remain unchanged. Calculation is made by varying number of blades and blade rotation. At the wind speed of 10 m/sec and the rotational speed of 100 rpm, the SKEA able to produce the power of 6.36 kW.